APPLICATION OF INTEGRAL EVALUATION SCALES IN PATIENTS WITH WIDESPREAD PURULENT PERITONITIS - Ярослав Миронович Лещишин; Андрей Игоревич Баранов; Константин Владимирович Потехин; Сергей Александрович Ярощук; Юрий Викторович Валуйских (Медицина в Кузбассе)
An objective assessment of the severity of the patient's condition allows for a comparative study of their results and, equally important, a more objective prediction of treatment outcomes. In our work, we use several scales to assess the severity of patients with advanced purulent peritonitis and predict the mortality of patients in the sample, these are SAPSII, SOFA, MODS and MPI.